Criteria of the European and National Identity from the Elites’ View-point - Veličkaitė, Kristina; Matonytė, Irmina; Morkevičius, Vaidas (Sociologija. Mintis ir veiksmas, 2009)
The article is based on the data from the “IntUne” project survey of elites carried out in spring of 2007 in 15 European Union countries (N= 1780). The Lithuanian, Polish and French elites’ samples, analyzed in depth, have N= 120. The aim of the study is to assess the importance of selected criteria for elites’ definition of a true “national” and of a true “European”. The theoretical framework of the article is based on the dichotomy of national and European identity. The hypotheses are: 1) in elites’ view European identity dwells on the same criteria as national identity; 2) definitions of the national and European identities by the Lithuanian elites employ the same criteria as the European elites in general and the French and Polish elites in particular. Results show that 1) among the elites, the criteria of national and European identity are very similar, yet the salience of factors are perceptibly higher in the case of the national identity; 2) each country’s elites have slightly diverging criteria of national and European identities.